2013
DOI: 10.3354/meps10410
|View full text |Cite
|
Sign up to set email alerts
|

Trophic interactions and ecological stability across coral reefs in the Marshall Islands

Abstract: Coral reef assemblages, trophic interactions, and food web stability were examined across a remote and densely populated atoll, in the Republic of the Marshall Islands (RMI). The biomass of sharks, large-bodied piscivores, and secondary invertebrate consumers was expectedly larger in the absence of major human populations. Less intuitively, we report a doubling in the density and biomass of small-bodied acanthurids with significant human presence, whereas large-bodied parrotfishes were halved. These trends pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 52 publications
3
48
2
Order By: Relevance
“…The human influence metric does not take account of resource abundance metrics, such as reef area, nor of human infrastructure and travel time, or livelihood alternatives such as agriculture and animal husbandry among other socioeconomic attributes that should influence fishing pressure . Given the better predictions of human influence and environmental factors in other regions (Friedlander et al 2003, Brewer et al 2013, Houk & Musburger 2013, Williams et al 2015, Maire et al 2016, Mellin et al 2016a, the weaker responses found here suggests the need for an evaluation of fishing pressure and the factors that promote it at smaller spatial scales. Good models must account for various local factors influencing the balance between fish production and human impacts.…”
Section: Environmental Habitat and Human Influencesmentioning
confidence: 78%
“…The human influence metric does not take account of resource abundance metrics, such as reef area, nor of human infrastructure and travel time, or livelihood alternatives such as agriculture and animal husbandry among other socioeconomic attributes that should influence fishing pressure . Given the better predictions of human influence and environmental factors in other regions (Friedlander et al 2003, Brewer et al 2013, Houk & Musburger 2013, Williams et al 2015, Maire et al 2016, Mellin et al 2016a, the weaker responses found here suggests the need for an evaluation of fishing pressure and the factors that promote it at smaller spatial scales. Good models must account for various local factors influencing the balance between fish production and human impacts.…”
Section: Environmental Habitat and Human Influencesmentioning
confidence: 78%
“…With the exception of a few specialized species, scleractinian coral diversity has rebounded on a number of reefs affected by nuclear testing . As well, the size-frequency distribution, an indicator of biomass, of many fish taxonomic groups within former blast sites have been observed to be much greater than that of the surrounding waters unaffected by nuclear testing (Houk and Musburger 2013). While nuclear testing is devastating on an acute timescale, it may prove to be beneficial to the local ecosystem over a more chronic duration through human exclusion.…”
Section: Radiation Impactsmentioning
confidence: 99%
“…Indeed, these areas have been demonstrated to have quite diverse and thriving ecosystems that are often in a better ecological state when compared to similar areas where routine human activity is present (see Fig. 2; Gray and Rickard 1989;Whicker et al 2004;Davis 2007;Richards et al 2008;Houk and Musburger 2013). Thus, sites devoted to nuclear arms production and testing can still be considered a positive feature in maintaining biodiversity despite the potential for chronic health impacts in resident organisms.…”
Section: Radiation Impactsmentioning
confidence: 99%
See 2 more Smart Citations